Prevention, Early Detection, and Eradication of Benghal Dayflower in Field Nurseries - Robert H. Stamps (EDIS)
Benghal dayflower is an increasingly problematic weed that is federally designated as a noxious weed. This revised 10-page fact sheet provides nursery owners how to prevent, detect, and eradicate this invasive plant. Written by Robert Stamps and published by the UF Department of Environmental Horticulture, May 2011.